Bone mineral density and associated risk factors among female athletes: a cross-sectional study - Nur Syamsina Ahmad; Mohamad Shariff A. Hamid; Phaik, Jadeera Geok Cheong; Sareena Hanim Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2018)
Menstrual irregularity and disordered eating were previously identified as risk factors for low bone mineral density (BMD) in female athletes. Therefore, an investigation for more potential factors that could be associated with low BMD among Malaysian female athletes is required. The aim of this study was to assess the association of BMD with energy availability, body weight, body fat, estrogen level and bone loading status in female athletes and to what extent those factors predict BMD. Energy intake and expenditure, body weight, Bone Physical Activity Questionnaire (BPAQ) score and estrogen level were determined from 85 female athletes aged 18-30 years in this cross-sectional study. Bone mineral density was measured by using an ultrasound bone densitometry device at the calcaneus bone. The female athletes’ body weight and fat percentage were 56±9 kg and 27±6%, respectively and they were all eumenorrheic. Fifty three percent of them had low BMD (z- score < 0). Their mean energy intake (1291±33 kcal/day) was lower than energy expenditure (1807±34 kcal/day) which resulted in a low energy availability (29±1 kcal/day/kg FFM). BMD was positively associated with BPAQ score (r=0.4, p=0.000) and body weight (r=0.3, p=0.005) but negatively associated with energy expenditure (r=-0.4, p=0.000). There was no association of BMD with energy intake, energy availability, body fat percentage and estrogen level. In conclusion, BMD was associated with energy expenditure, body weight and BPAQ score among female athletes. Regression analysis showed that energy expenditure and BPAQ score were the main factors to predict BMD.